Examining the role of L2 proficiency in L2 reading-writing relationships - Agustín Llach, Mª Del Pilar (Estudios Ingleses de la Universidad Complutense, 2010)
The paper explores the relationship between reading and writing in young Spanish learners of EFL. Research acknowledges the reading-writing relationship, but studies dealing with L2 literacy skills are scarce, and results inconclusive. Participants were divided into a cohort of low proficient learners and another of low-mid proficient learners. Learners had to complete a reading comprehension test and write a timed composition. Results revealed that for the low proficient learners the relationship was not strong enough to be significant, whereas for the low-mid proficient learners we found a significant correlation. This finding highlights the importance of L2 proficiency in establishing the nature and magnitude of the relationship reading-writing, confirming thus previous research. The pedagogical implications of this result point to reading and writing as two separate but related instructional areas, so that they cannot be replaced by each other but should not be taught in isolation either.